(untitled) (UCC Student Medical Journal, 2026)
Introduction: Ramsay Hunt Syndrome (RHS) is a neurological disorder caused by the reactivation of latent varicella-zoster virus in the facial nerve. It often presents with ipsilateral facial palsy, otalgia, and vesicular eruptions. RHS is often misdiagnosed as Bell’s palsy, which results in delayed treatment and increases the risk of long-term complications. This case highlights a 38-year-old male initially diagnosed with Bell’s palsy whose symptoms persisted despite standard therapy. He later developed ear pain, discharge, vesicles, and gait instability, prompting a revised diagnosis of RHS. Methods: A comprehensive clinical assessment was conducted, including a detailed patient history, neurological and otologic examination, and laboratory investigations. Diagnostic imaging and serological tests confirmed varicella-zoster virus reactivation. The patient was treated with antiviral therapy (acyclovir), corticosteroids, and symptomatic pain management. Results: The patient initially presented with progressive facial nerve dysfunction refractory to Bell’s palsy treatment, and subsequently developed vesicular ear lesions and balance disturbances. Examination revealed asymmetric facial weakness, inflamed auricular vesicles, and an unsteady gait. Laboratory results confirmed RHS. Following initiation of antiviral and steroid therapy, symptoms improved, though residual facial weakness persisted. Conclusion: This case underscores the importance of early diagnosis of RHS in order to prevent long term complications. When diagnosing idiopathic Bell’s palsy, RHS should be considered, particularly when new otologic symptoms emerge. Unlike Bell’s palsy, RHS is associated with a lower rate of full recovery due to greater nerve degeneration. Clinicians should maintain a high index of suspicion for RHS in cases of persistent facial palsy, ensuring timely diagnosis and intervention in order to improve patient outcomes.